Evaluación agronómica y productiva de maíz (Zea mays l.) variedad iniap-176 a diferentes fuentes de fertilización nitrogenada complementaria en la granja experimental Laguacoto III, provincia Bolívar - Quinatoa Manobanda, Fanny Yessenia (2021)
The cultivation of maize worldwide is among the four staple foods on the planet as the main source of energy in multiple sub products of the Corn Valor Chain (CVM) for both human food and the large animal food industry. In Ecuador, the cultivation of soft and hard maize is fundamental within production systems because of its contribution to food security and sovereignty. On the Coast of Ecuador is an intensive system of monocultive and specifically crystalline corn for the animal industry. In the highs lands, there are varied production systems both for consumption in tender (Choclo) or dry and in varied uses of the food culture of the rural population. This research was carried out in the Experimental Farm Laguacoto III of the State University of Bolivar, Guaranda canton, Bolívar province at an altitude of 2640 m in a clay loam soil and in rainfed conditions. The nitrogen (N) and its sources are very important for improving crop productivity and is the most important and critical element for maize. The objectives in this research were: i) To measure the effect of five sources of N and a control on the main agronomic components of the maize variety INIAP 176 in the Laguacoto III and ii) To perform the Partial Budget Economic Analysis (AEPP) and calculate the Marginal Rate of Return (TMR). The Mathematical Model of Random Complete Block Design (DBCA) was applied with six treatments and four repetitions. The treatments constituted five sources of N such as Ammonium Nitrate, Calcium Nitrate, Urea, Ammonium Sulfate, Amides and a control without the application of N. The most relevant agronomic components were evaluated and recorded in the vegetative, reproductive and postharvest stages of the crop. The corresponding analysis of variance (ANOVAS), Tukey 5% test for the comparison and separation of treatment means, correlation analysis and linear regression of independent variables versus grain yield were performed, and the Partial Budget Economic Analysis (AEPP) and the Marginal Rate of Return (TMR) were performed. The response or effect of N sources were very different for most of the agronomic components evaluated. The independent variables that reduced yield were the percentage of stem lodging, percentage of small grain and the high content of calcium in the soil. The most important components with the best positive fit with yield were the highest averages of plant height, cob length and diameter, percentage of plants with two cobs, percentage of grain in second category, biomass yield and root volume. From the chemical, agronomic and economic point of view the best sources of N for corn variety INIAP 176 and in the agroecological zone of Laguacoto III were in its order Urea, Ammonium Sulfate and Amides. The INIAP 176 maize was adapted favorably in the agroecological zone of Laguacoto III with excellent yields of both grain and biomass, constituting a valid technological alternative for farmers and thus improve the efficiency of corn production systems in the territory.